Aktualisasi Makna Sakinah dalam Keluarga Single Parent - Lutfia Eka Ramadhani; Mar’atul Habibah; Mila Erliana (Jurnal Teologi Islam, 2026)
A harmonious family is an ideal concept in Islam that emphasizes peace, love, and affection within the household. Generally, this concept is built on the basis of a husband-wife relationship, but in social reality, many families are run by a single parent due to divorce, the death of a spouse, or other reasons. This study examines how the values ​​of harmonious family can be applied in single-parent families. Using a descriptive-qualitative approach, this paper describes the meaning of harmonious family in the context of single parenthood and relevant strategies for actualization, such as a strong foundation of faith, open communication, and structured life management. The results indicate that single-parent families can still achieve true peace and harmony as long as Islamic values ​​are the foundation of their upbringing and daily lives.